2016
DOI: 10.21037/asvide.2016.438
|View full text |Cite
|
Sign up to set email alerts
|

Nuss bar procedure: past, present and future

Abstract: Repair of pectus excavatum began at the beginning of the 20 th century before endotracheal intubation was standard practice. Surgeons therefore developed techniques that corrected the deformity using an open procedure via the anterior chest wall. Initial techniques were unsatisfactory, but by the 1930s the partial rib resection and sternal osteotomy technique had been developed and was used in combination with external traction post-operatively to prevent the sternum from sinking back into the chest. In 1949, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
49
0
9

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(58 citation statements)
references
References 14 publications
0
49
0
9
Order By: Relevance
“…With the left thoracoscopic approach, we found that the surgical eld of view was wide enough to clearly observe the entire pleural cavity, left lung, blood vessel, heart, pericardium, mediastinum and diaphragm; hence, serious complications can be avoided. Several authors favored placing the trocar in the middle axillary line [14], [25]. However, we found that the trocar placed in the middle axillary line can result in vision that can be hindered by the heart, lungs, and diaphragm, especially in cases of asymmetrical severe PE.…”
Section: Discussionmentioning
confidence: 73%
“…With the left thoracoscopic approach, we found that the surgical eld of view was wide enough to clearly observe the entire pleural cavity, left lung, blood vessel, heart, pericardium, mediastinum and diaphragm; hence, serious complications can be avoided. Several authors favored placing the trocar in the middle axillary line [14], [25]. However, we found that the trocar placed in the middle axillary line can result in vision that can be hindered by the heart, lungs, and diaphragm, especially in cases of asymmetrical severe PE.…”
Section: Discussionmentioning
confidence: 73%
“…The U-shaped metal rod is often a 1-2 cm, flattened appliance that is threaded under the concavity of the sternum using an introducer to avoid both the pericardium and internal thoracic vessels [1,2].…”
Section: Discussionmentioning
confidence: 99%
“…Bilateral thoracoscopy allows direct visualization during pericardial dissection and bar introduction, which minimizes the risk of cardiopulmonary injury . The use of the correction index has recently been considered a reliable alternative to the conventional Haller index, because it can represent the degree of ribcage deformity more accurately without being affected by the width of the chest . The risk of metal allergy should not be underestimated, as it has been reported to occur in 2 per cent of patients undergoing Nuss procedure .…”
Section: Discussionmentioning
confidence: 99%
“…2 The use of the correction index has recently been considered a reliable alternative to the conventional Haller index, because it can represent the degree of ribcage deformity more accurately without being affected by the width of the chest. 3,4 The risk of metal allergy should not be underestimated, as it has been reported to occur in 2 per cent of patients undergoing Nuss procedure. 5 However, the routine use of a less allergenic titanium bar has not been advocated, due to the lack of elastic recoil, as compared to surgical steel, which is an essential property to protect children from unexpected trauma.…”
Section: Discussionmentioning
confidence: 99%